Chronicle - Archives of Acoustics, Editorial Board (Archives of Acoustics, 1999)
1. General Assembly of Delegates of Polish Acoustical Society 2. Dissertation: Determination of the spatial distribution of spectral components of ship’s noise [in Polish], 23 December 1998 by Paulina Bittner 3. Dissertation: Quality of synthesized organ pipe sounds versus parameters of the digital waveguide models [in Polish], 15 December 1997 by Sławomir Zieliński